CONSTRUCTIVE CRITICISM OF ULUM AL-QURAN, HADITH STUDIES, AND ISLAMIC JURISPRUDENCE FROM A CONTEMPORARY SCIENTIFIC PERSPECTIVE - Maltifal; Aljamaedi; Yanfaunnas; Muksinin, Muksinin; Syahruddin (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2026)
Classical Islamic sciences face global challenges in maintaining their relevance and epistemological authority amidst the development of modern scientific methodologies that emphasize historical criticism, interdisciplinary analysis, and responsiveness to contemporary issues. This article argues that apologetic or defensive approaches are no longer adequate, and that constructive criticism based on contemporary scientific frameworks is an intellectual necessity. The research objectives are threefold: 1) to map the points of dialogue and tension between classical epistemology and modern methods; 2) to offer constructive criticism to strengthen the validity of these sciences; and 3) to propose an integrative framework for responsible revitalization. To achieve these goals, this study employs a qualitative-interdisciplinary method through a systematic critical-analytical literature study, involving internal textual analysis, critical dialogue with hermeneutics, sociology of knowledge, and applied ethics, as well as normative synthesis. The results map the key dialectics and propose a model of